Rhythmic Teaching of E.Jaques-Dalcroze (Eurhythmic) - Pētersone, Ginta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This year Jaques-Dalcroze Institute Geneva is celebrating its 100th anniversary and also the 150 years of its founder, the Swiss educator Emile Jacques-Dalcroze (1865-1950). At the beginning the pedagogical teaching method using connection between music and movement was named rhythmic gymnastics. The aim was to improve students' sense of rhythm and music. These exercises have been developed by creating a new set of methods, which was named the rhythmic. To emphasize the importance of this new teaching technique E.Jaques-Dalcroze named it rhythmical musical education. To avoid the confusion with overall term for analysing rhythm in the music, the newly created education technique was called eurhythmic in English. In Latvian the term Eurythmie is better known as method of Rudolf Steiner, which is partly similar to rhythmic, but mainly based on cognitions of anthroposophy. In other European languages the teaching of E.Jaques-Dalcroze is called rhythmic. Rhythmic is based on a unity between music and movement. Assuming that the movement is the foundation to all live expressions, the rhythm of music becomes the synchroniser between music and movement, thus having an influence on both sensomotor, both cognitive and emotional level. Musical experience is becoming more personal and the analysis of music is not torn apart from life, because it is perceived by bodily movements and integrates hearing, visual, tactile, kinesthetic and vestibular senses. The aim of this article is to reflect the establishment of Jaques-Dalcroze rhythmic teaching, its basic principles, further development and implementation in Latvian education.